Implementation of the Strengthening Project for Pancasila Student Profiles (P5) in Grade IV B at Baiturrohman GMI Elementary School in Jember - Maghfirotul Firmaning Lestari; Tituk Ihlilawati (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2023)
The purpose of this research is to examine the implementation of the Pancasila Student Profile Strengthening Project (P5) in Grade IV B at Baiturrohman GMI Elementary School in Jember. The research method used in this study is a qualitative research method with naturalistic observation, where the researcher aims to observe the learning enthusiasm and understanding of students during the implementation of the Pancasila Student Profile Strengthening Project (P5). The results of this research show that the implementation process of the Pancasila student profile strengthening project in Grade IV B is effective. In this project, students have the opportunity to learn about important themes or issues such as climate change, anti-radicalism, mental health, culture, technology entrepreneurship, and democratic life. This allows students to take real actions in responding to these issues according to their learning stages and needs. This is evident through the products produced by students, which align with the expectations of their teachers.